Developing deep understanding of teacher education practice through accessing and responding to pre-service teacher engagement with their learning. Issue 5 (20th October 2019) - Fletcher, Tim; Ní Chróinín, Déirdre; O'Sullivan, Mary
ABSTRACT: In this research we examined the ways we accessed and responded to students' engagement with a set of pedagogical principles of teacher education focused on meaningful physical education. The research was cross-cultural, taking place in universities in Country 1 and Country 2. Self-study of teacher education practice (S-STEP) methodology guided collection and analysis of the following data over one year: lesson planning and reflection documents, and critical friend and 'meta-critical friend' interactions. Findings indicate the value in teacher educators becoming more intentional and systematic in how they access student perspectives related to engagement with learning experiences of pedagogical innovations in pre-service teacher education, while also emphasising the challenges in doing so. The concepts of reflection on- and in-action provided a framework for understanding how being more intentional about accessing student perspectives can be enacted in teacher education practice. Our experiences demonstrate how focusing on student engagement can support the professional learning of teacher educators through enabling a deeper understanding of the challenges faced in being responsive to students' engagement with their learning.